Radiation risk from lung cancer screening - Rampinelli, Cristiano; De Marco, Paolo; Bellomi, Massimo (Annals of Translational Medicine, 2017)
We have read with interest the editorial of Mascalchi and colleagues, on our study “Exposure to low dose computed tomography for lung cancer screening and risk of cancer: secondary analysis of trial data and risk-benefit analysis” (1).